The evolving landscape of ER-LD contact sites - Kumar, Akhil; Yadav, Surabhi; Choudhary, Vineet (Frontiers in Cell and Developmental Biology, 2024)
Lipid droplets (LDs) are evolutionarily conserved dynamic organelles that play an important role in cellular physiology. Growing evidence suggests that LD biogenesis occurs at discrete endoplasmic reticulum (ER) subdomains demarcated by the lipodystrophy protein, Seipin, lack of which impairs adipogenesis. However, the mechanisms of how these domains are selected is not completely known. These ER sites undergo ordered assembly of proteins and lipids to initiate LD biogenesis and facilitate establishment of ER-LD contact sites, a prerequisite for proper growth and maturation of droplets. LDs retain both physical and functional association with the ER throughout their lifecycle to facilitate bi-directional communication, such as exchange of proteins and lipids between the two organelles at these ER-LD contact sites. In recent years several molecular tethers have been identified that bridge ER and LDs together including few proteins that are found exclusively at these ER-LD contact interface. Here, we discuss recent advances in understanding the role of factors that ensure functionality of ER-LD contact site machinery for LD homeostasis.